1990
DOI: 10.1007/bf03183914
|View full text |Cite
|
Sign up to set email alerts
|

Protein and mineral concentrations in tubers of selected genotypes of wild and cultivated Jerusalem-artichoke (Helianthus tuberosus, asteraceae)

Abstract: Nineteen wild and cultivated genotypes of Jerusalem-artichoke (Helianthus tuberosus) whose tubers are used as food were analyzed for protein and mineral content at three stages ofgrowth. The protein content ofthe tubers is comparable to or higher than that ofother common root-type crops. Adequate macrominerals of calcium, magnesium, and phosphorus werefound in Jerusalem-artichoke. Potassium and sodium concentrations were higher than other root crops. Trace elements (manganese, zinc, and copper) were present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
1
11
0
2
Order By: Relevance
“…Potassium and sodium concentrations of tubers of Jerusalem artichokes were higher than other root crops. In addition, adequate macrominerals of calcium, magnesium, and phosphorus were found in Jerusalem artichoke tubers (Seiler 1990). Trace elements (manganese, zinc, and copper) were present in adequate amounts, with iron content higher than several other root crops (Seiler 1990).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Potassium and sodium concentrations of tubers of Jerusalem artichokes were higher than other root crops. In addition, adequate macrominerals of calcium, magnesium, and phosphorus were found in Jerusalem artichoke tubers (Seiler 1990). Trace elements (manganese, zinc, and copper) were present in adequate amounts, with iron content higher than several other root crops (Seiler 1990).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, adequate macrominerals of calcium, magnesium, and phosphorus were found in Jerusalem artichoke tubers (Seiler 1990). Trace elements (manganese, zinc, and copper) were present in adequate amounts, with iron content higher than several other root crops (Seiler 1990). Ekholm et al (2007) reported that Jerusalem artichoke tubers contained 83.4% water, 3210 mg=100 g K, 3210 mg=100 g Ca, 112 mg=100 g Mg, and 280 mg=100 g P. In addition, the same plants contained 1.8 mg=100 g Fe, 1.0 mg=100 g Cu, 0.2 mg=100 g Mn, 1.4 mg=100 g Zn, 0.001 mg= 100 g Co, 0.154 mg=100 g Ni, 0.002 mg=100 g Se, 0.7 mg=100 g Al, 0.003 mg=100 g Cd, and 0.007 mg=100 g Pb (Ekholm et al 2007).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Wild and cultivated Jerusalem artichoke genotypes appear to contain adequate protein and macro-and micro-minerals to contribute significantly towards a nutritionally balanced diet (Seiler 1990 ).…”
Section: Nutritive/medicinal Properties Tuber Nutrients/phytochemicalsmentioning
confidence: 99%